2021
DOI: 10.1186/s13017-021-00372-1
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of pre-hospital triage tools for major trauma: a systematic review with meta-analysis and net clinical benefit

Abstract: Background We conducted a systematic review to evaluate and compare the accuracy of pre-hospital triage tools for major trauma in the context of the development of the Italian National Institute of Health guidelines on major trauma integrated management. Methods PubMed, Embase, and CENTRAL were searched up to November 2019 for studies investigating pre-hospital triage tools. The ROC (receiver operating characteristics) curve and net clinical benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 49 publications
0
30
0
3
Order By: Relevance
“…Even though criteria based solely on trauma dynamic and patient's characteristics seem to be the most relevant cause of overtriage [ 15 , 16 ], it is important not to underestimate the condition of grade C patients since age and MOI showed to correlate with injury severity [ 6 , 17 , 18 ]. Some studies even suggested the need for specialized geriatric trauma teams and specific triage criteria for elderly patients and children [ 19 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though criteria based solely on trauma dynamic and patient's characteristics seem to be the most relevant cause of overtriage [ 15 , 16 ], it is important not to underestimate the condition of grade C patients since age and MOI showed to correlate with injury severity [ 6 , 17 , 18 ]. Some studies even suggested the need for specialized geriatric trauma teams and specific triage criteria for elderly patients and children [ 19 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent and comprehensive study regarding the TRENAU classification is a systematic review with meta-analysis conducted by Gianola et al[ 19 ] . which compares the TRENAU score with other triage tools (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To fulfill such a demand, the training of Military Medicine clinicians has been observed to be the most efficient and optimal solution as they are already trained in first aid, TCCC, and other emergency medicine practices. The success of prehospital care relies on accurate triage where less accurate triage can unnecessarily lower treatment passed the acceptable standard of care or deviate from the correct diagnoses [18]. The utilization of Military Medicine clinicians is essential as they are already trained in triage practices and are more likely to accurately triage prehospital casualties as Military Medicine has extensive experience in triage out of other medical specialties.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…In France, prehospital EMS is physician-led, from call reception to on-scene intervention, where care is provided by a mobile medical team (MMT). This model of EMS was shown to be an effective way to optimize prehospital triage 7,8 and this could partly be due to the use of a Vittel criteria-based grading system 7,9 . However, the factors associated with undertriage and their impact on patient-centered outcomes have yet to be investigated in this physician-led prehospital system.…”
Section: Introductionmentioning
confidence: 99%